Effect of Cyclophosphamide in Histological Features of Cerebrum in Chick Embryos - Sultana, Shabana; Doshi, M. A.; Jayasree, N.; Chandrupatla, Mrudula (International Journal of Innovative Research in Medical Science, 2017)
Cyclophosphamide is an Alkylating Agent and it comes under the category of Nitrogen Mustards, which is used commonly in the treatment different types of Cancers or Carcinomas or Neoplasms (Goodman and Gilman 9th edition 1996).It was synthesized and Introduced in the year 1854 and its properties were elaborately observed and described by 1887. Cyclophosphamide is administered in the treatment of Acute Lymphoblastic Leukemia, Chronic Lymphocytic Leukemias, Hodgkin’s Lymphoma, Non-Hodgkin’s, Lymphoma, Multiple Myeloma, Neuroblastoma, Breast Cancer etc. It is also a potent Immuno Suppressive Drug. It has been used for the Control of Organ Rejection after Transplantation, Wegner’s Granulamatosis, Rheumatoid Arthritis, Nephrotic Syndrome in Children. In the present study fertilized eggs were administered with Cyclophosphamide and histological features of Cerebrum were studied after 20 days. Cyclophosphamide cytotoxicity results in reduction of multiplication of cell activity associated with malformations and embryonic death. Injection of the drug causes decrease of mitotic activity which produces deformities.